Conceptualising love in Yorùbá socio-cultural contexts - Tayo Adebayo (Journal of Language and Pragmatics Studies, 2026)
The examination takes a novel approach to how the Yorùbá culture conceptualises love. The rationale for the study is that, while many studies examine proverbs related to love and marriage, none have focused solely on proverbs about love. The scarcity of such studies has left a vital gap in research exploring how love is contextualised in both romantic and non-romantic contexts. The present study, therefore, investigates how the Yoruba tribe contextualises love within its socio-cultural milieu. Guided by Searle's (1969) speech act theory and Brown and Levinson’s (1987) politeness theory, the study collected data through purposive sampling, gathering Yoruba love proverbs from two Yoruba language tutors. The study’s findings demonstrate that Yorùbá love proverbs and expressions comment on love in both romantic and non-romantic contexts. Love in a romantic context depicts love as a feeling and commitment, while love in a non-romantic context presents love as a foundational factor in human relationships and love as a means of negotiating one’s needs at the expense of others. This research contributes to African cultural studies by demonstrating how foundational cultural concepts like love are encoded, transmitted, and negotiated through oral traditions, offering necessary insight into Yorùbá worldview and social relationality.